Forest and Land Fire Disaster Learning Assisted by Google Sites for Disaster Literacy of Students Senior High School in Tebo Regency - Risma Martiyani; Dewi Liesnoor Setyowati; Tjaturahono Budi Sanjoto; Hariyanto Hariyanto; Erni Suharini (JPG (Jurnal Pendidikan Geografi), 2026)
Forest and land fires are a frequent disaster in Indonesia and cause multidimensional impacts, ranging from environmental damage and health problems to disruptions to education. In areas prone to forest and land fires, such as Tebo Regency, Jambi Province, recurring haze events indicate that mitigation efforts have not been fully balanced by increased disaster literacy, especially among students. This condition also shows that disaster learning in schools still needs to be strengthened through the use of learning media that is contextual and relevant to local conditions, including the use of digital media. This study aims to describe the implementation of forest and land fire mitigation learning using Google Sites and to evaluate students' disaster literacy levels after participating in the learning. The study used a quantitative approach with a pre-experimental design in the form of a one-shot case study. The research sample consisted of 27 11th-grade students of SMA11 Tebo Regency, selected through purposive sampling. Data collection techniques included observation of learning implementation, tests to measure basic disaster literacy and functional disaster literacy, and questionnaires to measure communicative literacy and critical disaster literacy. Data analysis was conducted using descriptive quantitative methods. The results of the study indicate that forest and land fire mitigation learning assisted by Google Sites can be implemented effectively and received a positive response from students. The level of student disaster literacy is in the high category across all indicators, with the majority of students able to understand the basic concepts of forest and land fires, apply mitigation information, communicate disaster messages, and demonstrate critical thinking skills on forest and land fire issues. These findings indicate that the use of Google Sites as a contextual learning medium has the potential to comprehensively improve student disaster literacy and support the strengthening of disaster preparedness in forest and land fire-prone areas.